A new approach for classification of stretch-shortening cycle: Beyond 250 ms of ground contact time - Ünver, E.; Konsuk Ünlü, H.; Yildiz, A. E.; Cinemre, S. A. (Journal of Sports Sciences, 2024)
The stretch-shortening cycle (SSC) has been classified into fast (<250 ms) and slow (>250 ms) groups based on ground contact time (GCT) threshold values. However, there are gaps in the literature on how the 250 ms threshold value was found and which variables affect it. The purpose of this study is to validate the 250 ms threshold by investigating the factors affecting this threshold. For this purpose, force-time variables during a drop jump (DJ) with a force plate and achilles tendon (AT) muscle-tendon unit mechanical properties using shear-wave elastography in 46 recreationally active men were analysed. A regression tree analysis was conducted using R studio to classify GCT with correlated variables (p < 0.05). The new GCT threshold values (GCT < 188 ms, 188 = GCT < 222 ms and GCT = 222 ms) were found according to the lowest root mean square error of approximation value (0.1985) at reactive strength index. Comparisons of GCT groups showed significant differences in force, time, power variables and AT length (p < 0.05). AT length is the main variable differentiating GCT groups: Short AT results in a short GCT and long AT results in a long GCT. This study reveals that SSC can be classified into three groups using new GCT threshold values, offering a new perspective for SSC assessment.